Suplementasi Mineral Sulfur Pada Ransum Tongkol Jagung Amoniasi Dan Pengaruhnya Terhadap Kecernaan Secara In Vitro - Elihasridas Elihasridas; N Jamarun; M Zain; Y Marlida (Universitas Andalas, 2012)
An experiment was conducted to evaluate the effect supplementation of mineral sulphur on the digestibility of ammoniated corn cobs ration. The objective of this experiment is to determine the optimum level of sulphur supplementation to in vitro digestibility of rations. Rations consisted of 50% ammoniated corn cobs and 50% concentrate. As treatments, was various levels of sulphur at0, 0,13, 0,16, 0,21 and 0,32% of DM basis. Parameters measured included: digestibility of DM, OM, CP and fiber fractions. Data were statistically analyzed by variance analysis in a block randomized design. Results showed that the treatments gave highly significant (P<0,01) effect on the digestibility. Digestibility of DM. OM, CP and fibers fractions increased as increasing level of sulphur supplementation. The best digestibility was found on 0,16% level of sulphur supplementation.